Mime-based creative drama implementations for exploring gestural interaction - Unluer, Adviye Ayca; Ozcan, Oguzhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
We observed that students are used to employ the graphical user interface (GUI) elements such as icons and texts in gestural interaction designs, depending on their prior experiences. However, prior knowledge of GUI design often leads the students to create cliche and impractical designs for gestural interaction. To solve the problem, our study aims to explore feedback as an alternative education method, enhanced by an exercise we call gestural shadow mapping', which is based on the art of mime, within the concept of creative drama. Using a basic setup for shadow representation, a group of design students practised expressing prepared visual compositions as gestural shadow maps for an audience of their peers. After several observations, feedback showed that the method based on gestural shadow mapping does afford students a better understanding of gestural interaction, free from the inhibitions of their prior experiences of GUIs and the limitations of current commercial examples.
Keywords: gestural interaction; design education; creative drama; mime; ENTERTAINMENT-EDUCATION; IMPACT; ARTS; Art